Use of Rice Husk-Bark Ash by Grinding to Fineness in Concrete - Rukzon, Sumrerng (Engineering and Applied Science Research, 2015)
The objective of this research is to study properties of Rice Husk-Bark Ash by grinding to fineness for use to replace Portland cement type I. Rice Husk-Bark Ash is a by product from heating process in thermal power plants. A thermal power plant with a capacity of 300 ton per day. It is burned at 800-900° C and therefore the quality of the materials is quite uniform because of control to burn. Rice Husk-Bark Ash has been hardly use due to big particle size and little pozzolanic materials property. This research is to use the Rice Husk-Bark Ash was ground until the particle size retained on sieve No. 325 was 3.24%. 8.08% and 23.76% by weight. Then. were use to replace Portland cement type I at 20% by weight of cementitious materials to cast mortar and mortars were tested to determine compressive strengths at the age of 7.28 and 60 days. The test results showed that the strength activity indice of mortars with to use replace Portland cement type I with Rice Husk-Bark Ash by grinding fineness are higher than 75 percent of the control mortar at the ages of 7 days or 28 days. And the test results showed that the development of Rice Husk-Bark Ash by grinding to fineness resulted in a high pozzolanic materials property and could be used in concrete work.